2021
DOI: 10.1002/ejp.1878
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress in early childhood and the risk of adolescent spinal pain with impact

Abstract: Background: Spinal pain (SP), including neck and back pain, is common and often associated with poor mental health and reduced quality of life of adolescents. Contemporary understanding of SP favours a biopsychosocial approach, and emerging evidence suggests the stronger influence of psychological rather than other factors. Objectives:We aimed to investigate if experiencing psychological distress in early childhood increases the risk of spinal pain with impact during adolescence.Methods: 1175 adolescents from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Our results are compatible with other studies that investigated the association between psychological distress and neck pain, despite the different assessment scales for psychological distress [ 41 – 43 ]. Some prospective studies have suggested that psychological distress as a meaningful predictor of the development and persistence in neck pain [ 26 , 44 , 45 ]. To our knowledge, few studies prior to this work have examined this association among healthcare students, despite the high prevalence of psychological distress and neck pain in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are compatible with other studies that investigated the association between psychological distress and neck pain, despite the different assessment scales for psychological distress [ 41 – 43 ]. Some prospective studies have suggested that psychological distress as a meaningful predictor of the development and persistence in neck pain [ 26 , 44 , 45 ]. To our knowledge, few studies prior to this work have examined this association among healthcare students, despite the high prevalence of psychological distress and neck pain in this population.…”
Section: Discussionmentioning
confidence: 99%